2017
DOI: 10.1007/s00404-017-4290-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of slow release insemination on pregnancy rates: report of two randomized controlled pilot studies and meta-analysis

Abstract: PurposeA modified application technique of intrauterine insemination (IUI) is slow release insemination (SRI), first described by Muharib et al. (Hum Reprod 7(2):227–229, 1992), who postulated higher pregnancy rates with a slow release of spermatozoa for 3 h.MethodsTo investigate this approach, two randomized controlled, cross-over pilot studies were performed from 2004 to 2006 in Israel and Germany to compare SRI with the standard bolus IUI. We aimed to present the results and perform a meta-analysis on avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 27 publications
(43 reference statements)
1
14
0
Order By: Relevance
“…Metaanalysis of all eligible studies for SRI (n = 3) revealed a combined relative risk for pregnancy after SRI of 2.64 (95% CI 1.04-6.74), P = 0.02). In conclusion, these results lend support to the hypothesis that the pregnancy rate might be improved by SRI compared to the standard bolus technique [39].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Metaanalysis of all eligible studies for SRI (n = 3) revealed a combined relative risk for pregnancy after SRI of 2.64 (95% CI 1.04-6.74), P = 0.02). In conclusion, these results lend support to the hypothesis that the pregnancy rate might be improved by SRI compared to the standard bolus technique [39].…”
Section: Discussionsupporting
confidence: 77%
“…Marschalek et al aimed to present the results and perform a meta-analysis on available data for SRI [39]. Univariate comparisons of pregnancy rates were performed using one-tailed z tests for method superiority.…”
Section: Discussionmentioning
confidence: 99%
“…This multicentre, randomised, controlled cross-over trial was conducted in women with infertility and/or the need for semen donation who were eligible for IUI in 11 fertility centres across Europe. As already stated in a prior pilot study 22 , the cross-over design was chosen because it has been shown to give results comparable to those from studies with a parallel design, and, thus, to be a valid approach for infertility trials 23,24 .…”
Section: Methodsmentioning
confidence: 99%
“…Patients were recruited between October 2012 and June 2017. Women were included if they fulfilled all of the following criteria: 22 (i) primary or secondary infertility, defined as a couple's failure to conceive after 12 months of attempting conception; (ii) age 20-40 years; (iii) tubal patency as diagnosed by hysterosalpingography, hystero-contrast-sonography (hycosy) or dye test with a maximum time interval between tubal testing and the woman's enrolment into the study of 12 months; (iv) since the total motile sperm count is a major factor which influences pregnancy changes after IUI 25 , a minimum of 10 million motile sperm cells/ millilitre (mio/ml) after preparation; (v) infertility due to anovulation and/or endometriosis and/or the need for semen donation and/or unexplained infertility. In this context, unexplained infertility is defined as the absence of a definable reason for a couple's failure to conceive after 12 months of attempting conception despite a detailed evaluation of ovulation, tubal and uterine abnormalities and male infertility factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation